2021
DOI: 10.5152/j.aott.2021.20076
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic effects of full endoscopic spine surgery via transforaminal approach in elderly patients with lumbar spinal stenosis: A retrospective clinical study

Abstract: Objective This study aimed to investigate the therapeutic effects of full endoscopic spine surgery on clinical and radiological outcomes in elderly patients over 70 years with lumbar spinal stenosis, without any obvious segmental instability. Methods A total of 47 patients (27 males, 20 females; the mean age=74.23±5.16) above 70 years who underwent a transforaminal percutaneous endoscopic decompression with the diagnosis of lumbar spinal stenosis, were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Although PETD can achieve good surgical efficacy in the treatment of LSS, its surgical indications remain controversial [ 9 , 37 ]. Our study showed that old age, severe grade of surgical-level disc degeneration and more disc degeneration levels increased the incidence of complications, which indicates that patients with such conditions should be cautious about PETD.…”
Section: Discussionmentioning
confidence: 99%
“…Although PETD can achieve good surgical efficacy in the treatment of LSS, its surgical indications remain controversial [ 9 , 37 ]. Our study showed that old age, severe grade of surgical-level disc degeneration and more disc degeneration levels increased the incidence of complications, which indicates that patients with such conditions should be cautious about PETD.…”
Section: Discussionmentioning
confidence: 99%
“…Guodong Yin [87] 2021 Following removal of the disk protrusion, ventral facet of the SAP, and ligamentum flavum, the traversing nerve root and dural sac were exposed with adequate mobility and good pulse, indicating complete decompression. It was necessary to eliminate residua along the entire traversing nerve root up to the lateral recess.…”
Section: Intra-operative Assessment Of Epd 1) Epd In Pteld For Ldhmentioning
confidence: 99%
“…PTED can remove the herniated disc and the osteophytes, hypertrophic ligament flavum, and hyperplastic articular process. Studies have shown that PTED is safe and effective, with the advantages of less trauma, faster rehabilitation, and less adjacent segment degeneration compared to traditional open surgeries (3)(4)(5). With the widespread use of this surgical technique, surgical complications, and clinical outcomes of PTED have gained more attention.…”
Section: Introductionmentioning
confidence: 99%